Implementation of the Javanese Alphabet Educative Game "Jable Board" to Increase Students' Learning Interest and Motivation (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2023)
Students' low interest in learning Javanese alphabet makes their learning outcomes not optimal in Javanese language subjects, so interesting learning methods are needed to motivate and increase their learning interest. Jable Board is a scrabble-based Javanese alphabet board game. This medium is useful for preserving, reviving, and supporting the learning of the Javanese alphabet to make it easier to understand. Based on the product validation test, qualitative data were obtained in the form of sound response, button accuracy, and battery life, which were classified as good. Quantitative data is also obtained from teachers and generation Z questionnaires, which are very good, so this game is feasible to implement. The aim is to determine the effectiveness of Jable Board in improving student learning outcomes. The research was conducted using a quasi-experimental method with 36 students in class X-E1, SMAN 3 Sidoarjo. The results of a student questionnaire about Jable Board, which showed that it was able to increase interest in learning by 86%, increase pretest and posttest scores by 24.18%, and receive positive responses from the school, showed that Jable Board was able to attract interest in learning and motivate students to learn Javanese alphabet, which can improve student learning outcomes.